Analisis Kuat Tekan Beton Self Compacting Concrete (SCC) dengan Kadar Superplasticizer yang Bervariasi - Ridwan, Muhamad; Putra, Sony Adiya; Halimatusadiyah (Sekolah Tinggi Teknologi Dumai, 2024)
In concrete construction work, compaction is a job that must be done in the implementation of reinforced concrete construction. Compaction aims to reduce air trapped in the fresh concrete mixture so that homogeneous concrete can be produced and air voids do not occur in the concrete. So self-compacting concrete technology is an alternative that can be taken. So, conducting research on concrete test specimens with the planned compressive strength of concrete using a mixture of additives, and comparing it with concrete without the addition of additives, is a difficulty for planners in determining the characteristic compressive strength and slump flow value of Self-Compacting Concrete. So a laboratory simulation of these conditions was carried out, by making a number of normal concrete and concrete test specimens with the addition of additives in the form of superplasticizer 1.6% and 2% of the cement weight. The maximum compressive strength value of concrete at 2% superplasticizer content was obtained, namely 340 kg/cm2 at the age of 28 days with a fas value of 0.34 and an average compressive strength of 327 kg/cm2. For a superplasticizer content of 1.6%, an average compressive strength of 316 kg/cm2 is obtained. Normal concrete has an average compressive strength of 305 kg/cm2 so that concrete the planned compressive strength of 300 kg/cm2.